Implementasi Sistem Pelacakan Kendaraan Bermotor Menggunakan Gps Dan Gprs Dengan Integrasi Googlemap - Yazid Dul Muchlisin; Jazi Eko Istiyanto (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2011)
Abstract— Vehicle tracking system using GPS and GPRS integration googlemap provide information that is maximized with the technology of GPS (Global Positioning System) receiver which can indicate the position of the vehicle with the map and the ability of the appointment of direction and position coordinates (x, y or latitude, longitude) textually and visual at any location. Vehicle tracking system is built using equipment GIS (Geographic Information System) and dedicated to smartphones which support Global Positioning System (GPS), as well as portable computers, using General Packet Radio Service (GPRS) as a connection to the internet. The hardware used is a smartphone that supports GPS with supporting tools used are GoogleMaps, Notepad + +, NetBeans IDE 6.5.1, Mysql, Java (J2ME), PHP, JavaScript. The results of this system in the form of tracking system capable of monitoring the movement of vehicles on an ongoing position by utilizing GPS and GPRS as the sender of the wireless data and Internet connections. Keywords— GIS, GPS, GPRS, googlemaps, J2ME,